Use of chest CT scan scoring system for diagnostic and therapeutic decision making in pleural effusion - Lejla Burnazović-Ristić; Besim Prnjavorac; Tamer Bego; Maida Rakanović-Todić; Lejla Prnjavorac (Medicinski glasnik, 2019)
Aim: To investigate the usage of chest computed tomography (CT) scan score for improvement in diagnostic and treatment efficacy of repetitive pleural effusion. Methods: CT scan scoring system was used as a part of diagnostic procedures in patients with repetitive pleural effusion. Patients with at least two pleurocentesis were included in the study. Chest and abdominal ultrasound, chest x-ray, bronchoscopy, biochemical, microbiological and cytological analysis of pleural fluid specimen were performed for all patients. Results: In a two-year period (during 2017-2018) 79 patients were analysed, 27 (34.17%) female and 52 (65.82%) male patients. Malignant pleural diseases were confirmed in 32 cases (40.5%), nonmalignant pleural effusions in 38 (48.1 %) cases, and nine (11.4%) patients rested without exact cause of pleural effusion after two pleurocenteses. Binary regression model showed odds ratio of 1.314; CI 95% 1.119-1.543) (p=0.00088). Confirmed malignancies with pleural effusion were in high correlation with the number of points in CT scan score. Conclusion: CT scan scoring system was helpful for diagnostic and treatment decision making in patients with repetitive pleural effusion.
Keywords: CT scan; malignancy; pleural effusion; scoring system